Measuring lifetimes of Polycyclic Aromatic Hydrocarbon fragments. (July 2015) - Wolf, M; Alexander, J D; Stockett, M H; Giacomozzi, L; de Ruette, N; Schmidt, H T; Zettergren, H; Cederquist, H
Synopsis: We investigate collisions of Polycyclic Aromatic Hydrocarbon cations with noble gases at center-of- mass energies close to 100 eV and below. Charged fragments are stored in a new version of the electrostatic ion beam trap ConeTrap. After storage for different well-defined times we extract the ions and use a reflectron based time-of-flight mass spectrometer to analyse the ion mass distributions. This will give information on secondary decay channels and the lifetime of the initially trapped fragment.